Evaluation of increasing peptone blend on nursery pig performance from 15 to 40 lb - Marcio Antonio Dornelles Goncalves; Joshua R Flohr; Steven S Dritz; Michael D Tokach; Joel M DeRouchey; Robert D Goodband; Jason C Woodworth (Kansas Agricultural Experiment Station Research Reports, 2013)
A total of 270 pigs (PIC 327 × 1050, initially 15.7 lb BW) were used in a 28-d trial to evaluate the effects of increasing levels of a new peptone blend by-product on nursery pig growth performance. The product is the result of the pharmaceutical extraction of chondroitin sulfate from bovine cartilage and processing to form the peptone blend, which was mixed with soybean hulls and drum-dried. Pigs were weaned at 21 d of age and were fed a common pelleted diet for 5 d prior to the start of the experiment. Each treatment had 8 replicate pens and 6 or 7 pigs per pen. The 5 experimental treatments were: (1) a diet with 1% blood meal and 2% select menhaden fish meal (positive control), (2) a diet with no added specialty protein source (negative control), (3) a diet containing 4% peptone blend, (4) a diet containing 8% peptone blend, or (5) a diet containing 12% peptone blend. Experimental diets were fed for 14 d, then a common Phase 2 diet was fed for an additional 14 d to determine the residual treatment effects on growth performance. From d 0 to 14, pigs fed increasing peptone blend had increased (linear, P<0.001) ADFI but poorer (linear, P<0.001) F/G. Pigs fed the positive control diet had increased (P = 0.04) ADFI compared with pigs fed the negative control diet. From d 14 to 28, when pigs were fed a common diet, pigs previously fed increasing peptone blend had increased (linear, P = 0.03) ADFI and poorer (linear, P = 0.001) F/G. Similar to d 0 to 14 data, pigs previously fed the positive control diet had increased (P = 0.05) ADFI compared with pigs previously fed the negative control diet from d 14 to 28. Overall (d 0 to 28), pigs fed diets with increasing peptone blend for the first 14 d had increased (P<0.001) ADFI and poorer F/G (P<0.001) with no differences in ADG (P = 0.87). Pigs fed the positive control diet had increased (P = 0.01) overall ADFI compared with pigs fed negative control diet, with no differences (P>0.17) in ADG or F/G. Based on these results, the peptone blend is not a suitable replacement for blood meal and select menhaden fish meal in nursery pig diets from 15 to 24 lb. Up to 4% of the peptone blend was a suitable replacement for soybean meal in the negative control diet, which contained no specialty protein sources.; Swine Day, Manhattan, KS, November 21, 2013
Keywords: Swine day; 2013; Kansas Agricultural Experiment Station contribution; no. 14-044-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1092; Growth performance; Nursery pig; Peptone blend; Specialty protein sources